Muslim societies’ ambivalence to Arabic: reasons, manifestations and consequences - Selim, Nadia (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
The relationship between Arabic and Islam was conceived when the commandments of Allah were revealed to Muslims in Arabic. In fact the Quran, entirely in God’s voice, clearly stipulates that “We have sent it down as an Arabic Quran so that you [people] may understand” (12:2). Naturally, Arabic is a component of various daily religious practices such as the recital of the Holy Quran, the five daily prayers and exaltations of Allah. Therefore, Arabic has held a sacrosanct position in the hearts of Muslims for centuries and the Muslim civilization embraced it as a Lingua Franca. However, academic literature paints a picture tainted by great degrees of ambivalence to Arabic in modern Muslim societies. This emergent ambivalence is evident at individual and institutional levels and indicates that the relationship between Arabic and Islamic education is no longer a straight forward one. More importantly, this ambivalence can explain the stagnation that afflicts the Arabic teaching profession and leaves known problems unresolved. This article will highlight the drift away from Arabic in modern Muslim societies and how this has invariably set Arabic language programs on a downwards spiral.